Caudillo de España: Viriathus, Trajan, Franco - Baldwin, Oliver (Rome and Iberia : Inspirations and Connections throughout History, 2021)
The dictatorship of General Franco in Spain resorted to two characters of ancient Iberian history to promote Franco’s authoritarianism: Viriathus and Trajan. In the early years of the regime, Viriathus was often called “caudillo de los españoles”. The anachronic distinction was obviously meant to mirror Franco’s own title as Caudillo de España. Trajan, on the other hand, appeared as an Iberian conqueror and excellent, military, ruler, thus serving as a predecessor to another Iberian army general in power: Franco himself. These lines analyse how Trajan and Viriathus appeared, in Francoist propaganda and education, as two complementing precedents (internal and external, local and universal) of the greatest and final Caudillo de España, Franco.